“Cover the Fire” or Live in the Dusk - Pardue, Derek (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2022)
Informed by recent fieldwork with “Muslim youth” in Aarhus, Denmark, West African migrants in Lisbon, Portugal and personal experiences of mobility in both cities, I deploy dusk as a sensorial epistemology and fiction as a complementary aesthetic methodology as I attempt to write the city (creatively) back into the (critical) urban. Forays into fiction are pertinent, because it is through imagination and the creativity of textual expression that many find their voice and emerge from (daily) routine when confronted with the night. The image-texts presented are intended not as momentous highlights but as provocative suggestions of the nocturnal banal in terms of urban presences, borders and human-environment relationships. The overarching premise is that the difference of dusk is not a loss or necessarily a waning, but rather a generative force of meaning and belonging.